2014
DOI: 10.1055/s-0034-1383314
|View full text |Cite
|
Sign up to set email alerts
|

S1-Guideline: Management of Late-term and Post-term Pregnancy

Abstract: Scope and Purpose of the Guideline Statement of problemThe mean duration of a normal pregnancy, calculated from the 1st day of the last menstrual period, is 280 days or 40 + 0 weeks of gestation (GW).A pregnancy prolonged by more than 14 days, in other words, a pregnancy lasting 294 days or 42 + 0 GW or more, is defined by the WHO and FIGO as prolonged, post-term or post-mature pregnancy. The period between 40 + 0 and 41 + 6 GW is referred to as late-term pregnancy.More than 40 % of all pregnant women give bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Pregnant women beyond 40 + 0 weeks of gestation form a rather large and sensitive group. According to the American College of Obstetricians and Gynecologists 2014 [16] the likelihood for placental insufficiency is even higher in this cohort. A Cochrane database by Middleton et al, 2020 [18] was able to show an association between induction of labor and a significant perinatal risk reduction for women with prolonged gestation.…”
Section: Discussionmentioning
confidence: 78%
“…Pregnant women beyond 40 + 0 weeks of gestation form a rather large and sensitive group. According to the American College of Obstetricians and Gynecologists 2014 [16] the likelihood for placental insufficiency is even higher in this cohort. A Cochrane database by Middleton et al, 2020 [18] was able to show an association between induction of labor and a significant perinatal risk reduction for women with prolonged gestation.…”
Section: Discussionmentioning
confidence: 78%
“…Also, some researchers reported that the rate of operative vaginal deliveries increased with delivery after 40 weeks, and the higher incidence of 3rd or 4rd degree lacerations, secondary postpartum bleeding, and prolonged labor were observed between 40 and 42 weeks, compared with before 40 weeks of gestation (1,14,19).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the World health organization (WHO) definitions, postdate delivery lasting 42 weeks or more is referred to postterm, and the pregnancies between 40 and 41 + 6 weeks as late-term deliveries (1). Full term pregnancy is defined by the American Congress of Obstetricians and Gynecologists as 39 to 40 weeks of gestation (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Labor induction begins at 41 weeks in post-term pregnancies, according to national protocol (Khooshideh et al, 2017; Weiss et al, 2014). After 40 weeks, more than 40% of pregnant women give birth, and roughly 15% to 20% after 41 weeks.…”
Section: Introductionmentioning
confidence: 99%